Activity Diagram Modeling For Online Pedicab Ordering Information System Design - Anggoro, Ario Satyo; Laudryna A’aliya Shalma Agustin; Reza Christian Saragi (Kirana Publisher (KNPub), 2025)
This study addresses shifting urban mobility trends as digital platforms gain prominence while traditional transport like the becak remains essential for reaching densely populated neighborhoods. The research aims to develop an Android‑based online becak booking system using UML to systematically define comprehensive functional requirements and workflows. The methodology comprised requirement analysis, a Waterfall‑based SDLC, and UML Use Case and Activity Diagrams to outline interactions among administrators, customers, and drivers and to specify feature workflows. The resulting design supports user registration, authentication, seamless booking, detailed real‑time location tracking, cost and time estimation, continuous feedback and reporting. Efficiency is achieved through fully automated order lifecycles and robust data security via strict login verification and authorization controls. Additionally, GPS-powered nearest-becak search and an easy-to-use UI improve inclusive mobility. Future enhancements include field testing, user‑centric UX studies, and machine‑learning integration for optimized driver assignment and predictive arrival‑time prediction.